Capitalising on mobile instant messaging for undergraduates business empowerment / Che Faridah Che Mahmood ...[et al.] - Che Mahmood, Che Faridah; Omar, Nazihah; Adnan @ Abdullah, Norshaieda; Zakaria, Nor Balkish (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA (UiTM) Shah Alam, 2019)
Mobile Instant Messaging (MIM) or Instant Messaging (IM) via various web-based applications like WeChat, Viber, WhatsApp (WA) and Snapchat have gained much attention. It allows mobile phone users to access instant messaging services right from their smartphones. Despite various general publications indicating the advantages of mobile business, ranging from the start-up cost, flexibility, mobility up to inventory, the MIM’s application via mobile businesses are still scarce. The aim of this study was to examine the realm of MIM usage as a platform for mobile business among undergraduates in Malaysia by examining the uses of MIM for mobile business and to identify the perceived advantages of MIM as a platform for mobile business. An online questionnaire was designed and randomly distributed among identified undergraduates who have actively engaged in mobile business. The results show that MIM is frequently used to advertise and sell products most needed by undergraduates. Among the perceived advantages of MIM as a platform for mobile business is its cost effectiveness. In addition, undergraduates can easily and conveniently start-up mobile businesses and generate income simply via a mobile device and a mobile number as it is indeed preferable for reaching a general audience.